Protección laboral en la vejez del limitado físico, síquico o sensorial en el ordenamiento jurídico colombiano (2012)
ABSTRACT: The need for effective legal protection of the elderly with disabilities is currently being discussed. In this paper, the author analyzes if the labor protection mechanisms for these people are physically, psychologically, and sensorially adequate. Likewise, the author analyzes if the constitutional and legal regulations aimed at protecting the elderly must ensure the satisfaction of the basic needs of such people and the effective enjoyment of a dignified life in terms of labor and pensions. With this in mind, extensive and thorough review and interpretation of the regulations and constitutional jurisprudence was conducted in order to determine if the aging-related policies included in our Political Charter are being developed.